Investigation of Engineering Properties of Blast Furnace Slag Additive Mortars - Osman Günaydın; Kadir Güçlüer; Hüseyin Boran (MANAS: Journal of Engineering)
Cement, water and fine aggregate mixture is called mortar. Mortar samples suitable for the desired purpose can be obtained by adding various additives to the mortar samples. In this study, instead of standard sand, blast furnace slag (BFS) was used at 10%, 20% and 30% by weight in mortar samples. In order to determine the mechanical properties of the samples, compressive and flexural strength tests were applied. For the electrical resistivity values, a device with constant 30V voltage was prepared and the electrical resistivity values were measured. To determine the freeze-thaw resisting properties, it was applied sodium sulfate experiment. As a result, it was seen that the best values were obtained from 30% BFS additive samples in all series. The highest resistivity values are in the sample with 30% BFS doped with 0.1856 ohm.m and 0.268 ohm.m values. The highest freeze-thaw resisting value was seen in the sample with 30% BFS with 1.35%.